Towards agroecological living landscapes: First experiences from CIMMYT-Zimbabwe - Chimonyo, Vimbayi Grace Petrova; Matangi, Dorcas (International Maize and Wheat Improvement Center, 2022)
In Zimbabwe farm inputs are very expensive and climate change impacts are severe. The CGIAR initiative Transformational Agroecology across Food, Land, and Water Systems will build on the agroecological policy framework already in place and on several projects currently promoting agroecological principles. With coordination provided by the International Maize and Wheat Improvement Center (CIMMYT), the initiative will help build agroecological living landscapes in two territories with contrasting conditions and landscapes. In this video by the CIMMYT team, farmers and partners in these territories share their expectations about diversifying agricultural production through a mixed farming approach and about enhancing their capacity to adapt to climate change.